(untitled) (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2024)
Zusammenfassung Im Mittelpunkt dieses Interviews stehen die Motivation für die Gründung des Humboldt Center for Transdisciplinary Studies im chinesischen Changsha und die modellierende epistemologische Kraft, die von Humboldt für die wissenschaftliche Arbeit im Bereich von TransArea Studies sowie allgemein transdisziplinärer Wissenschaftskonzepte ausgeht. Hierin zeigt sich Humboldt als Quelle wissenschaftlicher Inspiration. Abstract This interview is about the motivations behind the foundation of the Humboldt Center for Transdisciplinary Studies at Hunan Normal University in Changsha (China) and about the epistemological power created by Alexander von Humboldt in the field of TransArea Studies and, in general, in transdisciplinary scientific approaches. Humboldt is seen as a fountain of inspiration. Resumen Esta entrevista discute las razones que llevaron a la fundación del Humboldt Center for Transdisciplinary Studies de la Hunan Normal University en Changsha, China, y la fuerza epistemológica que ejerce la práctica científica de Alejandro de Humboldt sobre los Estudios Transareales así como sobre concepciones transdisciplinares en el campo de las Humanidades. Se enfoca a Humboldt como una fuerza inspiradora en este campo.